The new role of musculoskeletal ultrasound in the treat-to-target management of juvenile idiopathic arthritis. (25th January 2021) - Gohar, Faekah; Windschall, Daniel
Abstract: This article reviews the role of musculoskeletal ultrasound (MSUS) for the diagnosis, monitoring and treat-to-target management of JIA. Technological advancements in MSUS allow more precise evaluation of arthritis, tenosynovitis and enthesitis versus clinical examination alone, which may assist treatment decisions. In adult studies, serum and synovial biomarkers have correlated with MSUS findings. Within paediatric rheumatology, significant developments in the definition of normal and pathology, a necessity for the future integration of MSUS into treat-to-target management, have already been reached or are underway, which in turn could allow tighter control of disease activity and earlier identification of treatment response and failure, bringing the goal of 'precision medicine' closer. Additionally, the utility of MSUS for the evaluation of subclinical disease remains an unexamined area of interest. 'Ultrasound remission' combined with clinical assessment and immunological markers could therefore potentially improve the treat-to-target management of JIA.